Teaching Mathematics - Online versus Offline - UNGUREANU, Laura (Journal of Research in Educational Sciences; Vol 11 No 1 (2020): JRES Volume XI Issue 1(13), 2020DO - 10.14505//jres.v11.13.04, 2020)
Mathematical thinking involves the ability to reason in rigorously composed stages, each related to the previous ones but also the ability to concentrate on long-term attention. Within the professional training of a teacher, two sides are combined: the scientific and the pedagogical. It is obvious that a good teacher must be a person with a rich, well-founded scientific training, clearly superior to the level at which he teaches. This paper seeks to provide an overview of current trends in the development of mathematics teaching, especially in the current context of the pandemic, when teaching is done mainly online. The aim is to highlight the differences, advantages and disadvantages, between teaching mathematics under normal conditions, offline and online teaching. Teaching math online is a huge challenge for both teachers and students.